Microstructural and Mechanical Properties of the Anterolateral Ligament (ALL) of the Knee. Issue 7 (31st July 2020) - Castile, Ryan; Lake, Spencer; Brophy, Robert; Patel, Ronak
Objectives: The anterolateral ligament (ALL) of the knee has recently emerged as a potential contributor to rotational stability of the knee, with growing interest in ALL reconstruction as a supplement to anterior cruciate ligament reconstruction. The prevalence of the ALL in the knee has varied in anatomic dissection and imaging studies, raising questions about its importance as a knee stabilizer. The purpose of this study was to assess the microstructural and mechanical properties of the anterolateral knee, to better understand the ALL structure compared to the surrounding anterolateral capsule (ALC) and lateral collateral ligament (LCL). A polarized light imaging technique was used to quantify collagen fiber alignment simultaneously with measurement of tensile mechanical properties. Our primary hypothesis was that there is no difference in the microstructural and mechanical properties between the ALL and ALC. Our secondary hypothesis was that the properties of the LCL are different from the ALL and ALC. Methods: Twenty-five knee specimens from sixteen donors (five males, eleven females; mean age 45.6 +/- 6.4; age range 35-59 years; mean BMI 26.5 +/- 8.4) were obtained as determined by a priori power analysis. The anatomic technique to dissect the anterolateral knee structures was performed as described previously. Three tissue samples (LCL, ALL, and ALC) were harvested (Fig. 1). The ALL was taken as a quadrilateral piece of tissue starting posterior/proximal from the lateral femoral epicondyle and ending at the lateral border of Gerdy's tubercle. During gross dissection, the knee was assessed for the presence or absence of a distinct visible and palpable structure within the area defined as the ALL. Harvested samples were thinned to approximately 1-mm thick using a freezing-stage sliding microtome. Cross-sectional area was measured using a 3D laser scanning system. Four 0.8-mm diameter aluminum beads were attached to the sample surface to enable strain measurement. Mechanical testing was performed with preconditioning followed by both a stress-relaxation test and a quasi-static ramp to failure. Microstructural analysis was performed using transmitted circularly-polarized incident light and a high-resolution, division-of-focal-plane polarization camera. The average degree of linear polarization (AVG DoLP; i.e., mean strength of collagen alignment) and standard deviation of the angle of polarization (STD AoP; i.e., degree of variation in collagen angle orientation) were calculated for the region of interest of each sample. Statistical analysis was performed using Kruskal-Wallis test (assuming nonparametric data) with Dunn's correction for multiple comparisons. Results: Mechanical analysis of elastic moduli for the toe- and linear-region of the stress-strain curves showed no difference between the ALL and ALC but were significantly higher for the LCL (p<0.0001; Fig. 2). Microstructural analysis of the ALL and ALC during quasi-static ramp to failure showed no difference in AVG DoLP and STD AoP values at all strain levels (Fig. 3). Larger DoLP values (i.e., stronger collagen fiber alignment) were observed for the LCL than both the ALL and ALC (p<0.0001). Larger STD AoP values (i.e., more variation in collagen orientation) were observed for the ALL and ALC compared to the LCL (p<0.0001; Fig. 3). When looking at correlations between mechanical and microstructural properties (Fig. 4), we found clustering of the LCL data points at high linear modulus and AVG DoLP while the ALL and ALC data points were clustered together. Similarly, we found clustering of the LCL at high linear modulus and low STD AoP while the ALL and ALC were clustered together. Only three of 25 knee specimens (12%) were observed to have a distinct, ligamentous structure in the region of the ALL. Interestingly, these distinct ALL samples (outlined in black on figures) showed relatively larger elastic moduli, higher AVG DoLP, and lower STD AoP (i.e., uniform and organized collagen alignment) across the stress-strain curve compared to samples harvested from knees without a distinct ALL. The distinct ALL tissues were also seen clustered near the LCL data points in the correlation plots. Conclusions: Overall, there were no differences in the mechanical and microstructural properties between the ALL and ALC, while the LCL demonstrated different properties compared to both the ALL and ALC. Both the ALC and ALL show significantly weaker collagen fiber alignment and more variation in the direction of collagen fiber alignment compared to the LCL. These findings suggest that the ALL has similar properties to capsule (i.e., ALC). However, when a distinct ALL was present at dissection (12%), the data indicates stronger and more uniform collagen alignment suggestive of more ligament-type qualities. Further research is needed to more precisely define the prevalence and properties of distinct ALLs in the knee.